PENGARUH UTILITARIAN DAN HEDONIC SHOPPING VALUE TERHADAP IMPULSE BUYING DAN PENGARUHNYA TERHADAP REPURCHASE INTENTION PRODUK FASHION PADA TOKO ONLINE (Studi Kasus Pada Konsumen Toko Online Shopee di Kota Pontianak) - B2042161002, ATIKA ALIFIA FITRININGSIH TOBING (Universitas Tanjungpura, 2019)
This study examines the factors that influence the impulse buying and repurchase intention actions which consist of utilitarian shopping value factors and hedonic shopping value. This type of research includes associative research with the number of respondents as many as 100 people using Shopee's online product store in Pontianak City. This study uses Statistical Product and Service Solution (SPSS) analysis version 25.00 with a path analysis method. The results of the study succeeded in accepting the three hypotheses proposed and rejecting the other two hypotheses. Hedonic Shopping Value proved to have a significant influence on Impulse Buying, Hedonic Shopping Value proved to have a significant influence on Repurchase Intention, Impulse Buying proved to have a significant influence on Repurchase Intention. Conversely, Utilitarian Shopping Value proved to have no significant effect on Impulse buying, Utilitarian Shopping Value opened did not have a significant effect on Repurchase Intention.Keywords : impulse buying, repurchase intention, utilitarian shopping values, hedonic shopping value